Large-scale gene disruption in Magnaporthe oryzae identifies MC69, a secreted protein required for infection by monocot and dicot fungal pathogens. - Hiromasa Saitoh (Public Library of Science (PLoS), 2012)
To search for virulence effector genes of the rice blast fungus, Magnaporthe oryzae, we carried out a large-scale targeted disruption of genes for 78 putative secreted proteins that are expressed during the early stages of infection of M. oryzae. Disruption of the majority of genes did not affect growth, conidiation, or pathogenicity of M. oryzae. One exception was the gene MC69. The mc69 mutant showed a severe reduction in blast symptoms on rice and barley, indicating the importance of MC69 for pathogenicity of M. oryzae. The mc69 mutant did not exhibit changes in saprophytic growth and conidiation. Microscopic analysis of infection behavior in the mc69 mutant revealed that MC69 is dispensable for appressorium formation. However, mc69 mutant failed to develop invasive hyphae after appressorium formation in rice leaf sheath, indicating a critical role of MC69 in interaction with host plants. MC69 encodes a hypothetical 54 amino acids protein with a signal peptide. Live-cell imaging suggested that fluorescently labeled MC69 was not translocated into rice cytoplasm. Site-directed mutagenesis of two conserved cysteine residues (Cys36 and Cys46) in the mature MC69 impaired function of MC69 without affecting its secretion, suggesting the importance of the disulfide bond in MC69 pathogenicity function. Furthermore, deletion of the MC69 orthologous gene reduced pathogenicity of the cucumber anthracnose fungus Colletotrichum orbiculare on both cucumber and Nicotiana benthamiana leaves. We conclude that MC69 is a secreted pathogenicity protein commonly required for infection of two different plant pathogenic fungi, M. oryzae and C. orbiculare pathogenic on monocot and dicot plants, respectively.